2009
DOI: 10.1007/s00360-009-0381-1
|View full text |Cite
|
Sign up to set email alerts
|

Inside the guts of wood-eating catfishes: can they digest wood?

Abstract: To better understand the structure and function of the gastrointestinal (GI) tracts of wood-eating catWshes, the gross morphology, length, and microvilli surface area (MVSA) of the intestines of wild-caught Panaque nocturnus, P. cf. nigrolineatus "Marañon", and Hypostomus pyrineusi were measured, and contrasted against these same metrics of a closely related detritivore, Pterygoplichthys disjunctivus. All four species had anatomically unspecialized intestines with no kinks, valves, or ceca of any kind. The woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 49 publications
4
73
0
Order By: Relevance
“…Loricariid catfishes are resilient animals, which lack scales, and endure handling stress with little side effects. For example, P. disjunctivus in this and previous investigations (German 2009b;German et al 2010) always consumed food following handling. This is probably why this fish species (and its close relatives) are popular in the aquarium trade and are successful invaders in novel habitats.…”
Section: Tissues Used For Stable Isotope Analysissupporting
confidence: 59%
See 4 more Smart Citations
“…Loricariid catfishes are resilient animals, which lack scales, and endure handling stress with little side effects. For example, P. disjunctivus in this and previous investigations (German 2009b;German et al 2010) always consumed food following handling. This is probably why this fish species (and its close relatives) are popular in the aquarium trade and are successful invaders in novel habitats.…”
Section: Tissues Used For Stable Isotope Analysissupporting
confidence: 59%
“…Twenty-two adult Pterygoplichthys disjunctivus were captured by hand while snorkeling from the Wekiva Springs complex in north central Florida (28º41′48.9″ N,81°23′27.84″ W) (German 2009b). We housed the fish in pairs because preliminary observations suggested that the fish were less stressed and commenced feeding immediately when in the presence of conspecifics.…”
Section: Fish Collection and Maintenance In The Laboratorymentioning
confidence: 99%
See 3 more Smart Citations